Penggunaan Batu Gunung Patangdo Kapa’ Kabupaten Tana Toraja Dalam Campuran AC-BC - Noviana Debi; Rais Rachman; Alpius (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
The purpose of this study was to laboratory test the use of Mount Patangdo Kapa 'Rock in Tana Toraja Regency as a mixture of AC-BC by varying the use of asphalt with a content of 5.50% 5.50% 6.50% 6.50% 7.00% and testing the resistance. The mixture to immersion temperature. The methodology in this study used a method consisting of a series of characteristic tests for coarse, fine, filler, and asphalt aggregates, then designing the composition of the mixture, then proceeding to make the test object, namely the AC-BC mixture through the MIX Design experiment to obtain the value of the Residual Strength Index using the optimal asphalt content. . The results show that the characteristics of the pavement material in the form of Patangdo Kapa 'Mountain Rock'Tana Toraja Regency have met the 2018 Highways Standard Specification as material in road pavement, especially in AC-BC mixture through testing with characteristics and with asphalt content of 5.00%, 5.50%, 6.00%, 6.50%, and 7.00%. Marshall immersion test results of AC-BC mixture using optimum asphalt content of 6.00% obtained a residual strength index (IKS) / durability of 93.47%. So this shows that the test meets the requirements of at least 90% and meets the 2018 Highways Specifications.